Annemarie Schimmel's Phenomenology: an Approach to Religious Experience in Islamic Studies - Rokhmatul Khoiro Amin Putri; Sita Isna Malyuna; Hanun Asrohah; Muhammad Thohir; Cynthia Llanes (Yayasan Letiges Konsultan Sosial, 2025)
This study aims to analyze and explore the phenomenological approach in Islamic Studies from the perspective of Annemarie Schimmel, as well as her contribution to Islamic Studies. It aims to offer a deeper understanding of Islamic beliefs, practices, and spiritual experiences. The research uses a literature review (library research) with a historical figure study approach. The researcher collected data from scientific articles, journals, books, and relevant documents, which were analyzed descriptively and qualitatively using content analysis. The findings of this study reveal that Schimmel's phenomenology is an approach that seeks to understand and penetrate the essence of religion by first examining its phenomena and then delving into the deeper layers of human responses to God until reaching the most profound sacred essence of each religion the centre, the divine, or Deus absconditus. This approach aims to interpret the meaning of Islamic teachings as understood and experienced by its followers rather than based on preconceived notions or the researcher's observations. In practice, this approach employs the concentric ring model theory, which helps create a more empathetic and objective understanding of the religious experiences of Muslims. This theory can serve as a valuable tool for interfaith dialogue and enhancing the image of Islam in the Western world.